(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This comprehensive article delves into the intricate world of sentence construction, focusing on the relationship between sentence types and the intended purpose of expression. The writer skillfully navigates through the fundamental categories of sentences, shedding light on how each type serves a distinct communicative function. The introduction effectively captures the reader’s attention by emphasizing the pivotal role sentences play in communication. The subsequent exploration of declarative sentences provides a solid foundation, showcasing their prevalence in conveying straightforward information. The inclusion of examples enhances clarity and aids in illustrating the concept.